Heteroresistance to Amikacin in Carbapenem-Resistant Klebsiella pneumoniae Strains - Feiyang Zhang (Frontiers Media S.A., 2021)
Heteroresistance can lead to treatment failure and is difficult to detect by the methods currently employed by clinical laboratories. The aim of this study was to investigate the prevalence of the amikacin-heteroresistant Klebsiella pneumoniae strains and explore potential amikacin heteroresistance mechanism through whole-genome sequencing (WGS) and quantitative reverse-transcription PCR (qRT-PCR). In this study, 13 isolates (8.39%) were considered as amikacin-heteroresistant K. pneumoniae strains among a total of 155 K. pneumoniae strains. The majority of the heterogeneous phenotypes (11/13, 84.61%) was unstable and the minimal inhibitory concentrations (MICs) fully or partially reverted back to the level of susceptibility of the parental isolate. The frequency of heteroresistant subpopulation ranged from 2.94×10−7 to 5.59×10−6. Whole-genome sequencing and single-nucleotide variants (SNVs) analysis showed that there were different nucleotide and resultant amino acid alterations among an amikacin-heteroresistant strain S38 and the resistant subpopulation S38L in several genes. Quantitative reverse-transcription PCR analysis revealed that the increased expression of aminoglycoside resistance genes detected in amikacin-heteroresistant K. pneumoniae strains might be associated with amikacin heteroresistance. The findings raise concerns for the emergence of amikacin-heteroresistant K. pneumoniae strains and the use of amikacin as therapy for the treatment of multidrug-resistant K. pneumoniae strains.